Familial abnormalities of endocannabinoid signaling in schizophrenia - Köthe, Dagmar; Pahlisch, Franziska; Rohleder, Cathrin; Meyer-Lindenberg, Andreas; Leweke, F. Markus (The world journal of biological psychiatry, 2019)
Objectives: Epidemiological and experimental evidence suggests that the endocannabinoid system plays a pathophysiological role in schizophrenia. This is reflected by elevated cerebrospinal levels of the endocannabinoid anandamide in schizophrenia and its initial prodromal states.Methods: We analyzed plasma concentrations of anandamide, 2-arachidonoyl-sn-glycerol, palmitoylethanolamide and oleoylethanolamide from 25 twin pairs discordant for schizophrenia, six discordant for bipolar disorder and eight healthy twin pairs to determine hereditary traits.Results: Twin pairs discordant for schizophrenia or bipolar disorder had significantly higher levels of anandamide and palmitoylethanolamide compared to healthy twins (both P < 0.002). Non-affected twins discordant for schizophrenia, who developed a psychotic disorder within 5 years follow-up showed lower anandamide (P = 0.042) and 2-arachidonoyl-sn-glycerol levels (P = 0.049) than twins who remained healthy.Conclusions: We suggest that the protective upregulation of endocannabinoid signalling reflects either a hereditary trait or mirrors a modulating response to genetically influenced cerebral function involving, e.g., other neurotransmitters or energy metabolism.
Gesehen am 31.05.2019
Published online: 22 Mar 2018